Sequential Organ Failure Assessment Component Score Prediction of In-hospital Mortality From Sepsis - Gupta, Tushar; Puskarich, Michael A; DeVos, Elizabeth; Javed, Adnan; Smotherman, Carmen; Sterling, Sarah A; Wang, Henry E; Moore, Frederick A; Jones, Alan E; Guirgis, Faheem W (Journal of intensive care medicine, 2020)
Early organ dysfunction in sepsis confers a high risk of in-hospital mortality, but the relative contribution of specific types of organ failure to overall mortality is unclear. The objective of this study was to assess the predictive ability of individual types of organ failure to in-hospital mortality or prolonged intensive care. Retrospective cohort study of adult emergency department patients with sepsis from October 1, 2013, to November 10, 2015. Multivariable regression was used to assess the odds ratios of individual organ failure types for the outcomes of in-hospital death (primary) and in-hospital death or ICU stay ≥ 3 days (secondary). Of 2796 patients, 283 (10%) experienced in-hospital mortality, and 748 (27%) experienced in-hospital mortality or an ICU stay ≥ 3 days. The following components of Sequential Organ Failure Assessment (SOFA) score were most predictive of in-hospital mortality (descending order): coagulation (odds ratio [OR]: 1.60, 95% confidence interval [CI]: 1.32-1.93), hepatic (1.58, 95% CI: 1.32-1.90), respiratory (OR: 1.33, 95% CI: 1.21-1.47), neurologic (OR: 1.20, 95% CI: 1.07-1.35), renal (OR: 1.14, 95% CI: 1.02-1.27), and cardiovascular (OR: 1.13, 95% CI: 1.01-1.25). For mortality or ICU stay ≥3 days, the most predictive SOFA components were respiratory (OR: 1.97, 95% CI: 1.79-2.16), neurologic (OR: 1.72, 95% CI: 1.54-1.92), cardiovascular (OR: 1.38, 95% CI: 1.23-1.54), coagulation (OR: 1.31, 95% CI: 1.10-1.55), and renal (OR: 1.19, 95% CI: 1.08-1.30) while hepatic SOFA (OR: 1.16, 95% CI: 0.98-1.37) did not reach statistical significance ( = .092). In this retrospective study, SOFA score components demonstrated varying predictive abilities for mortality in sepsis. Elevated coagulation or hepatic SOFA scores were most predictive of in-hospital death, while an elevated respiratory SOFA was most predictive of death or ICU stay >3 days.